Christmas memories from Mississippi - McCord, Charline R.; Tucker, Judy H.; Waters, Wyatt (University Press of Mississippi, 2010)
This beautiful book of thirty-eight essays, illustrated by Mississippi's premier watercolorist Wyatt Waters, will ring true with treasured recollections of Christmases past. Remember the Christmas it snowed on the Mississippi Coast? Glen Allison recalls that miracle. Richard Ford and Waters tell exactly what they felt when they first laid eyes on a bicycle left under the tree by Santa Claus. These Mississippians celebrate Christmas pageants, the decorating, the family dinners--even as they recognize war and loss as part of our lives and sometimes part of our holidays. Christmas Memories from M.